Home countries' determinants of outward foreign direct investment (OFDI) in developing economies: Malaysian case / Rosfadzimi Mat Saad, Abd Halim Mohd Noor and Abu Hassan Shaari Md Noor - Mat Saad, Rosfadzimi; Mohd Noor, Abd Halim; Md Noor, Abu Hassan Shaari (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
With the advance of globalization, foreign direct investments, FDIs are no longer limited to the developed nations. Increasingly FDIs between developing countries are rivalling traditional FDIs. Outward Foreign Direct Investment, OFDI is one of the measures to indicate the performance and capability of developing countries enterprises in economic integration where border barriers are eliminated. Malaysia as a developing economy is undertaking OFDI due to the limitation of local resources and to search for new markets. Multinational corporations, MNCs seek from other countries mainly for cheap labour, low resource prices, and new market for their products and services. This paper studies the determinants of OFDI by Malaysian based MNCs. It focuses on the trends, patterns and domestic factors that push Malaysian firms to be involved in OFDI. It will also be looking at domestic drivers such as market size, export level, cost of skilled labours and the availability of natural resources in determining the factors influencing Malaysian OFDI. Simple multiple regression analysis is used in the study. The period of study is between 1980 and 2009. The findings in this study provide strong corroboration that domestic factors have significant impacts on OFDI performance. Furthermore, the study found evidence that export, market size, and cost of skilled labours are significant contributors of OFDI in Malaysia.